Rubber latex compound, manufacturing method of gloves, and gloves
Patent Information
- Application Number
- JP2021099314
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-06-15
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2041-06-15
AI Technical Summary
【0024】 以上説明したように、本発明のゴムラテックス配合物は、タッチパネル反応性に優れるとともに、高い柔軟性を有する手袋を製造することができる。また、このゴムラテックス配合物を用いて製造された手袋及び本発明の手袋は、タッチパネル反応性に優れるとともに、高い柔軟性を有する。
Smart Images

Figure 0007634264000005 
Figure 0007634264000006 
Figure 0007634264000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a rubber latex compound, a method for producing a glove, and a glove. [Background technology]
[0002] In recent years, the number of devices operated by touch panels has been increasing, both for home and industrial use. Such touch panels generally operate using a capacitive method. Capacitive touch panels operate by capacitive coupling caused by the transfer of electric charge between the human body (e.g., fingertips) and the touch panel. For this reason, for example, wearing gloves can weaken this capacitive coupling, reducing the responsiveness of the touch panel.
[0003] In order to prevent the reactivity of the touch panel from decreasing, it is necessary to impart conductivity to the gloves and change the capacitance, electric field, magnetic field, etc. of the touch panel that is in close proximity to or in contact with the gloves, so that the touch position can be detected. Known examples of gloves that have been imparted conductivity include gloves that are heat-molded using a rubber latex compound in which acid-treated carbon black is blended with rubber latex (see JP 2003-321581 A).
[0004] When the amount of carbon black added is large, the glove film tends to become hard. When the glove film becomes hard, the flexibility of the glove decreases, and problems with workability such as difficulty in gripping objects occur. In this rubber latex compound, the use of acid-treated carbon black prevents the carbon black from agglomerating and gelling in the compound, making it possible to achieve low resistance with a relatively small amount added. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2003-321581 A Summary of the Invention [Problem to be solved by the invention]
[0006] In order to reduce the resistance of the above-mentioned conventional rubber latex compound to a degree that does not reduce the reactivity of the touch panel, it is necessary to compound the amount of carbon black, for example, 20 parts by mass or more per 100 parts by mass of rubber latex. On the other hand, gloves molded for touch panel operation are required to have high flexibility. For this reason, gloves with a further reduced amount of carbon black are required.
[0007] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a rubber latex compound capable of producing gloves having excellent touch panel responsiveness and high flexibility, a method for producing gloves using the rubber latex compound, and gloves having excellent touch panel responsiveness and high flexibility. [Means for solving the problem]
[0008] In order to obtain high conductivity with a small amount of carbon black added, it is necessary to secure a large number of conductive paths in which the carbon black particles are connected to each other and extend. In order to secure such conductive paths, the present inventor focused on improving the compounding stability of carbon black in rubber latex, that is, suppressing aggregation and gelation caused by carbon black and improving dispersibility. Generally, conductive carbon black is unstable in rubber latex and has poor compounding stability. As a result, in a coating formed using a rubber latex and a rubber latex compound containing carbon black, aggregation due to carbon black is likely to occur, and the carbon black particles are difficult to connect to each other and extend. In other words, it becomes difficult to secure conductive paths. For this reason, it is considered that a large amount of carbon black needs to be added to obtain a desired conductivity. In response to this, the present inventor found that the compounding stability of carbon black can be significantly improved and the conductivity of the coating can be improved by adding an anionic surfactant, a nonionic dispersant, and a water-soluble polymer in appropriate amounts, and completed the present invention.
[0009] That is, the rubber latex compound according to one aspect of the present invention is a rubber latex compound for gloves mainly composed of rubber latex, to which carbon black, anionic surfactant, nonionic dispersant and water-soluble polymer are added, DBP oil absorption of the carbon black is 250 ml / 100 g or more and 600 ml / 100 g or less, and volatile content is 0.3 mass % or more and less than 1.0 mass %, the amount of the water-soluble polymer added relative to 100 mass parts of the carbon black is 8 mass parts or more and 50 mass parts or less, and the total amount of the nonionic dispersant and the water-soluble polymer added relative to 100 mass parts of the carbon black is 38 mass parts or more and 200 mass parts or less.
[0010] The rubber latex compound contains carbon black having DBP oil absorption and volatile matter within the above ranges, and therefore, it is easy to improve compounding stability and ensure the conductivity of the formed coating. The rubber latex compound contains a nonionic dispersant and a water-soluble polymer that satisfy the above-mentioned amounts, and further contains an anionic surfactant. This compounding can improve the compounding stability of the carbon black in the rubber latex compound. Therefore, in the coating formed using the rubber latex compound, it is easy to ensure conductive paths in which the carbon black particles are connected to each other, and a small amount of the compound shows high conductivity. Therefore, by using the rubber latex compound, it is possible to manufacture gloves that are excellent in touch panel responsiveness and have high flexibility.
[0011] The amount of carbon black added per 100 parts by mass of the solid content of the rubber latex is preferably 0.6 parts by mass or more and 9.5 parts by mass or less. By setting the amount of carbon black added within the above range, the conductivity of the formed coating can be increased while maintaining high flexibility.
[0012] The amount of the anionic surfactant added to 100 parts by mass of the solid content of the rubber latex is preferably 0.05 parts by mass or more and 1.0 parts by mass or less. By setting the amount of the anionic surfactant added to 100 parts by mass of the solid content of the rubber latex within the above range, the electrical conductivity can be increased while ensuring the stability over time of the rubber latex compound and the ease of manufacturing the glove.
[0013] The mass ratio of the nonionic dispersant to the anionic surfactant is preferably from 0.2 to 285. By setting the mass ratio of the nonionic dispersant to the anionic surfactant within the above range, the stability over time of the rubber latex compound, the dispersibility of carbon black, and the ease of manufacturing the gloves can be ensured, and the electrical conductivity of the gloves to be manufactured can be increased.
[0014] The total mass ratio of the nonionic dispersant and the water-soluble polymer to the anionic surfactant is preferably from 0.5 to 300. By adding the water-soluble polymer so that the total mass ratio of the nonionic dispersant to the anionic surfactant falls within the above range, the compounding stability and electrical conductivity of the carbon black can be further improved.
[0015] A method for manufacturing a glove according to another embodiment of the present invention includes a first dipping step of dipping a hand mold into a coagulant solution, a second dipping step of dipping the hand mold after the first dipping step into a rubber latex compound, and a drying step of drying the hand mold after the second dipping step, wherein the rubber latex compound is the rubber latex compound of the present invention.
[0016] The manufacturing method of the glove uses the rubber latex compound of the present invention, so that it is easy to secure conductive paths in which carbon black particles are connected to each other, and it is possible to manufacture gloves having excellent touch panel responsiveness and high flexibility.
[0017] A glove according to still another aspect of the present invention has a conductive portion exposed on an outer surface of at least a second finger region on the palm side, the conductive portion being mainly composed of rubber and containing carbon black, the amount of carbon black added to 100 parts by mass of the rubber being 0.6 parts by mass or more and 9.5 parts by mass or less, and a surface resistance value of the conductive portion being 10 3 Ω or more 10 8 It is less than Ω.
[0018] The glove has a high electrical conductivity with the surface resistance value of the conductive part being within the above range, while the amount of carbon black added to the conductive part is within the above range. In other words, it is considered that the glove has a large number of conductive paths in which the carbon black particles are connected to each other. Therefore, the glove has excellent touch panel responsiveness and high flexibility.
[0019] The glove may include a knitted glove body made of fiber, the knitted glove body containing conductive fiber, and the conductive part laminated on the outer surface side of the knitted glove body. By combining the knitted glove body containing conductive fiber with the conductive part in this manner, electrostatic discharge (ESD) can be suppressed, and explosion-proof properties that prevent fires and explosions due to flammable gases, steam, dust, etc. can be improved.
[0020] The volume resistivity of the conductive part is 10 3 Ω or more 10 8 By setting the volume resistivity of the conductive portion within the above range, it is possible to impart high explosion-proof properties to the glove while maintaining its flexibility.
[0021] Here, the term "major component" refers to the component with the highest content, for example, a component with a content of 50 mass% or more. "DBP oil absorption" refers to the amount of DBP (dibutyl phthalate) absorbed by 100 g of carbon black, and is the amount measured using a 9 g sample in accordance with ASTM D 2414.
[0022] The "volatile content of carbon black" can be measured by the following method. A magnetic crucible (diameter 15 mm, height 30 mm, capacity 10 mL) and a drop lid were baked at 950±20°C for 30 minutes, then cooled to room temperature (25°C) in a desiccator, and the mass (MA) of the magnetic crucible and the drop lid was weighed to an accuracy of 0.1 mg. Next, 2 g of carbon black was packed into the magnetic crucible to a height not exceeding 2 mm below the lid, and the drop lid was placed on top, and the mass (MB) was weighed to an accuracy of 0.1 mg. After that, the mixture was heated in an electric furnace at 950±20°C for 7 minutes, cooled to room temperature (25°C) in a desiccator, and the mass (MC) was weighed again to an accuracy of 0.1 mg, and the volatile content was calculated using the following formula 1. Volatile content [mass%] = (MB-MC) / (MB-MA) × 100 1
[0023] The "surface resistance" and "volume resistance" can be measured by the following method. When the conductive part is present on the palm in addition to the finger part, and the conductivity of the finger part and the palm part is the same, the surface resistance and the volume resistance are measured according to the EN standards EN16350 and EN61340-2-3:2016 8, respectively. The measurement sample is cut out from the part where conductivity (surface resistance) or explosion-proofness (volume resistance) is required (for example, the finger part, hereinafter also referred to as the "measurement target part"). However, when the conductive part is only the finger part, or when the conductivity of the finger part and the palm part is different, and the measurement sample cannot be taken from the measurement target part, the surface resistance is measured according to EN16350 and EN61340-2-3:2016 10, and the volume resistance is measured according to ANSI / ESD SP15.1-2005. Effect of the Invention
[0024] As described above, the rubber latex compound of the present invention can be used to produce gloves having excellent touch panel responsiveness and high flexibility. Furthermore, gloves produced using this rubber latex compound and the gloves of the present invention have excellent touch panel responsiveness and high flexibility. [Brief description of the drawings]
[0025] [Figure 1] FIG. 1 is a flow diagram showing a method for producing a glove according to one embodiment of the present invention. [Diagram 2] FIG. 2 is a schematic perspective view of a glove according to one embodiment of the present invention as viewed from the palm side. [Diagram 3] FIG. 3 is a schematic perspective view of the glove of FIG. 2 as viewed from the back of the hand. [Figure 4] FIG. 4 is a schematic front view of a glove different from that in FIG. 2, as viewed from the palm side. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0026] The rubber latex compound, the method for producing a glove, and the glove according to one embodiment of the present invention will be described in detail below.
[0027] [Rubber latex compound] A rubber latex compound according to one embodiment of the present invention is a rubber latex compound for gloves, which is mainly composed of rubber latex. The rubber latex compound contains carbon black, an anionic surfactant, a nonionic dispersant, and a water-soluble polymer.
[0028] <Rubber latex> The rubber latex is a homopolymer or copolymer of acrylonitrile butadiene rubber (NBR), acrylic rubber, urethane rubber, natural rubber (NR), isoprene rubber, chloroprene rubber, or the like, or a carboxy-modified polymer thereof, either alone or in combination.
[0029] The rubber latex is more stable with the carbon black in the compound when the rubber latex has a larger gel content. When the polymer chain of the rubber latex has fewer branches, the gel content decreases, and when the polymer chain has many branches, the gel content increases. In the case of NBR, the gel content of the rubber latex can be evaluated as the MEK insoluble content ratio. The lower limit of the MEK insoluble content ratio of the rubber latex is preferably 10% by mass, more preferably 20% by mass, and even more preferably 30% by mass. On the other hand, the upper limit of the MEK insoluble content ratio of the rubber latex is preferably 80% by mass, more preferably 75% by mass, and even more preferably 73% by mass. If the MEK insoluble content ratio of the rubber latex is less than the lower limit, the stability of the carbon black in the rubber latex compound may decrease. Conversely, if the MEK insoluble content ratio of the rubber latex exceeds the upper limit, the film-forming property of the coating by the rubber latex compound may decrease. Similarly, in the case of NR, the gel content can be evaluated as the toluene-insoluble content ratio, and the lower limit of the toluene-insoluble content ratio is preferably 50%. The upper limit of the toluene insoluble content is not particularly limited, but is preferably 90%, more preferably 85%.
[0030] Here, the MEK insoluble content can be measured by the following method. First, the rubber latex is diluted with ion-exchanged water so that the total solid content is 30% by mass. 5 g of this diluted latex is weighed into a glass petri dish with an inner diameter of 10 cm, and dried in an oven at 30°C for 15 hours to remove moisture, thereby obtaining a film with an average thickness of about 0.05 mm. The film is cut into test pieces of about 5 mm square, and the test pieces are measured so that the mass is about 0.2 g, and then the mass is measured with four significant digits (this mass is W [g]). The test pieces are placed in a #80 metal mesh basket (bottom surface about 2 cm square, about 9 g) whose mass has been measured in advance. Next, the basket containing the test pieces is immersed in 100 ml of methyl ethyl ketone (MEK) and left to stand at 23°C to 25°C for 24 hours. After standing, the basket is lifted from the MEK and gently shaken for 30 seconds to allow excess MEK to drip off. Furthermore, the basket containing the test pieces is dried at 30°C for 3 hours, then at 105°C for 30 minutes, and the total mass of the basket containing the test pieces is measured. The mass of the test pieces after drying is calculated from the difference with the mass of the cage that has already been measured (this mass is designated as B [g]). From the calculated mass, the individual insoluble fraction for this test piece is calculated using the following formula 2. This is performed for four test pieces, and the arithmetic average is designated as the insoluble fraction. The toluene insoluble fraction can also be measured in the same manner by replacing the above-mentioned MEK with toluene. Individual insoluble fraction [mass%]=B / W×100...2
[0031] <Carbon black> The lower limit of the DBP oil absorption of the carbon black used is 250 ml / 100 g, more preferably 300 ml / 100 g, while the upper limit of the DBP oil absorption of the carbon black is 600 ml / 100 g, more preferably 500 ml / 100 g. In the rubber latex compound, the DBP oil absorption of the carbon black is set to be equal to or greater than the lower limit, so that the aggregate structure of the primary aggregates of the carbon black can easily secure a conductive path. This makes it easy to ensure the electrical conductivity of the coating formed by the rubber latex compound (hereinafter, also simply referred to as "electrical conductivity"). If the DBP oil absorption of the carbon black is less than the lower limit, it becomes necessary to add a large amount of the carbon black to obtain electrical conductivity, and the flexibility of the coating formed by the rubber latex compound (hereinafter, also simply referred to as "flexibility") may be insufficient. Conversely, if the DBP oil absorption of the carbon black exceeds the upper limit, the dispersibility of the carbon black may decrease, and the compounding stability may decrease. An example of carbon black having a DBP oil absorption within the above range is Ketjen Black (registered trademark).
[0032] The lower limit of the BET specific surface area of the carbon black is 250 m 2 / g is preferred, and 500m 2 On the other hand, the upper limit of the BET specific surface area of the carbon black is 1500 m 2 / g is preferred, and 1200m 2 / g is more preferable. By making the BET specific surface area equal to or greater than the lower limit, the number of pores in the carbon black increases, and the number of conductive holes increases. In addition, the polymer molecules in the rubber latex enter the pores, thereby shortening the distance between the carbon black particles, and making it easier to develop electrical conductivity. On the other hand, if the BET specific surface area of the carbon black exceeds the upper limit, the dispersibility of the carbon black decreases, and compounding stability may decrease. The "BET specific surface area" refers to a value measured in accordance with ASTM D 3037.
[0033] The lower limit of the volatile content of the carbon black is 0.3% by mass, and more preferably 0.4% by mass. On the other hand, the upper limit of the volatile content of the carbon black is less than 1.0% by mass, and more preferably less than 0.9% by mass. The volatile content is related to the amount of functional groups such as carboxyl groups that the carbon black has. The fewer the functional groups, the higher the electrical conductivity, but the crystallinity of the carbon black increases, and the compounding stability may decrease. That is, if the volatile content is less than the lower limit, the compounding stability of the carbon black may decrease. Conversely, if the volatile content is equal to or greater than the upper limit, the electrical conductivity may decrease.
[0034] The ash content of the carbon black is preferably 0.9% by mass or less. The lower the ash content, i.e., the lower the amount of impurities, the higher the electrical conductivity. The lower limit of the ash content of the carbon black is not particularly limited and may be 0% by mass, but is usually about 0.01% by mass. The "ash content of carbon black" refers to a value measured in accordance with ASTM D 1506.
[0035] The pH of the carbon black is preferably 6 or more and 10 or less. By setting the pH of the carbon black within the above range, the conductivity can be increased. The pH of the carbon black can be measured by the following method. 1 g ± 0.01 g of carbon black was weighed to an accuracy of 0.01 g and collected in a 20 mL beaker, and then 1 mL of ethyl alcohol and 10 mL of distilled water that had been boiled in advance were added to prepare a carbon black dispersion liquid, which was then covered with a watch glass and allowed to cool for 60 minutes in a thermostatic chamber at 25°C. After confirming that the dispersion liquid was at 25°C, a pH meter calibrated with pH standard solutions of 4, 7, and 9 was used to read the indicated value 1 minute after the start of measurement, and this was taken as the pH value.
[0036] The lower limit of the amount of carbon black added relative to 100 parts by mass of the solid content of the rubber latex is preferably 0.6 parts by mass, more preferably 2 parts by mass, and even more preferably 3 parts by mass. On the other hand, the upper limit of the amount of carbon black added is preferably 9.5 parts by mass, more preferably 8 parts by mass, and even more preferably 7 parts by mass. If the amount of carbon black added is less than the lower limit, the conductivity may be insufficient. On the other hand, if the amount of carbon black added exceeds the upper limit, the flexibility may be insufficient, and for example, the operability of a touch panel may be deteriorated.
[0037] The carbon black is preferably prepared as a water dispersion. That is, the carbon black is preferably dispersed using the nonionic dispersant described later in detail, and then mixed with the rubber latex. By dispersing the carbon black with the nonionic dispersant and then mixing it with the rubber latex in this way, the dispersion stability of the carbon black in the rubber latex compound can be improved. The dispersion stability of the carbon black contributes greatly to the conductivity, and if the dispersion stability is poor, aggregation due to the carbon black is likely to occur. This leads to a decrease in the conductivity of the glove obtained from the rubber latex compound, which in turn leads to an increase in the amount of the carbon black added, and the glove is hardened. The hardening of the glove means that the glove is less likely to conform to the object, i.e., the touch panel, etc., that is, the contact area for causing the touch panel to react due to its hardness is reduced, leading to a decrease in the reactivity of the touch panel.
[0038] In the aqueous dispersion, the lower limit of the amount of the nonionic dispersant added relative to 100 parts by mass of the carbon black is preferably 30 parts by mass, more preferably 40 parts by mass, and even more preferably 50 parts by mass. On the other hand, the upper limit of the amount of the nonionic dispersant added is preferably 150 parts by mass, more preferably 140 parts by mass, and even more preferably 130 parts by mass. If the amount of the nonionic dispersant added is less than the lower limit, the carbon black cannot be stably dispersed, and there is a risk that aggregation due to the carbon black occurs, resulting in a decrease in electrical conductivity. On the other hand, if the amount of the nonionic dispersant added exceeds the upper limit, there is a risk that it becomes difficult to form the glove.
[0039] <Anionic surfactants> The anionic surfactant can increase the stability of the rubber latex and prevent the occurrence of aggregation caused by the carbon black. If the anionic surfactant is not added, the stability of the rubber latex becomes insufficient, and there is a tendency that the carbon black will aggregate when added, the viscosity will increase and the rubber latex will not be usable as a rubber latex compound, and the film-forming property will deteriorate when a coating is formed by the salt coagulation method.
[0040] As the anionic surfactant, known surfactants can be used, such as fatty acid salts, alkyl sulfate salts, alkylbenzene sulfonates, alkylnaphthalene sulfonates, alkyl sulfosuccinates, polyoxyethyl alkyl sulfate salts, and naphthalene sulfonate-formaldehyde condensates.
[0041] The lower limit of the amount of the anionic surfactant added relative to 100 parts by mass of the solid content of the rubber latex is preferably 0.05 parts by mass, more preferably 0.1 parts by mass, and even more preferably 0.2 parts by mass. On the other hand, the upper limit of the amount of the anionic surfactant added is preferably 1.0 parts by mass, more preferably 0.8 parts by mass, and even more preferably 0.7 parts by mass. If the amount of the anionic surfactant added is less than the lower limit, there is a risk of occurrence of aggregation due to carbon black, a decrease in electrical conductivity associated therewith, a decrease in stability over time of the rubber latex compound, and the like. On the other hand, if the amount of the anionic surfactant added exceeds the upper limit, there is a risk of occurrence of the stability of the rubber latex being too high, and the coagulation property being rather decreased, making it difficult to manufacture the glove.
[0042] <Non-ionic dispersant> In the rubber latex compound, a non-ionic dispersant is used, which has high stability with respect to the carbon black.
[0043] The nonionic dispersant may be a known one, such as modified acrylic polymer, polyalkylene glycol, fatty acid ester, alkyl ether, or derivatives thereof, copolymers of styrenes such as styrene or α-methylstyrene with alkoxypolyalkylene glycol (meth)acrylic acid esters, copolymers of styrenes and maleic anhydride, etc. Among these, copolymers of styrenes such as styrene or α-methylstyrene with alkoxyalkylene glycol (meth)acrylic acid esters, such as styrene-methoxypolyethylene glycol methacrylate copolymers, or copolymers of styrenes and maleic anhydride, such as styrene-maleic anhydride copolymers, are preferred.
[0044] The present inventors have found that the stability of a rubber latex blend containing carbon black tends to depend on the ratio of an anionic surfactant for stabilizing the rubber latex and a nonionic dispersant for stabilizing the carbon black. That is, the lower limit of the mass ratio of the nonionic dispersant to the anionic surfactant is preferably 0.2, more preferably 1.0, and even more preferably 2.5. On the other hand, the upper limit of the mass ratio of the nonionic dispersant is preferably 285, more preferably 110, and even more preferably 45. By setting the mass ratio of the nonionic dispersant to the lower limit or more, it is possible to easily ensure the stability over time of the rubber latex blend, the dispersibility of carbon black, and the ease of glove production. In addition, if the mass ratio of the nonionic dispersant is less than the lower limit, aggregation due to the carbon black may occur in the rubber latex blend, resulting in a decrease in electrical conductivity. Conversely, if the mass ratio of the nonionic dispersant exceeds the upper limit, the carbon black particles are prevented from linking together during film formation, and there is a risk that sufficient conductive paths will not be formed.
[0045] The lower limit of the amount of the nonionic dispersant added relative to 100 parts by mass of the solid content of the rubber latex is preferably 0.6 parts by mass, more preferably 1 part by mass. On the other hand, the upper limit of the amount of the nonionic dispersant added is preferably 15 parts by mass, more preferably 10 parts by mass. If the amount of the nonionic dispersant added is less than the lower limit, aggregation due to the carbon black may occur in the rubber latex compound, resulting in a decrease in electrical conductivity. On the other hand, if the amount of the nonionic dispersant added exceeds the upper limit, the carbon black may be prevented from linking together during film formation, and sufficient electrical conductivity may not be formed.
[0046] <Water-soluble polymer> The stability of the carbon black in the rubber latex compound can be further improved by adding the water-soluble polymer. In particular, when carbon black with a large DBP oil absorption is used as the carbon black, the chain of the carbon black tends to become long, and the viscosity of the rubber latex compound tends to increase. In such a case, the water-soluble polymer has the effect of stabilizing the carbon black.
[0047] It has been mentioned that when the carbon black is prepared as an aqueous dispersion, it is preferable that the carbon black is dispersed using the nonionic dispersant. On the other hand, it is preferable that the water-soluble polymer is mixed with the rubber latex before the aqueous dispersion is mixed with the rubber latex. In other words, by adding the nonionic dispersant and the water-soluble polymer, it becomes possible to independently control the amount of the nonionic dispersant added to enhance the stability of the carbon black in the aqueous dispersion and the total amount of the nonionic dispersant and the water-soluble polymer added to enhance the stability of the carbon black in the rubber latex compound. Therefore, it is easy to enhance the stability of the carbon black in the rubber latex compound.
[0048] Examples of the water-soluble polymer include cellulose derivatives such as carboxymethylcellulose (CMC), methylcellulose, hydroxypropylcellulose, and hydroxyethylmethylcellulose, polyvinyl alcohol, polyvinylpyrrolidone, polyacrylic acid, polymethacrylic acid, polyacrylamide, poly-N-isopropylacrylamide, poly-N,N-dimethylacrylamide, polyethyleneimine, polyoxyethylene, poly(2-methoxyethoxyethylene), polyvinylsulfonic acid, polyvinylidene fluoride, amylose, gum arabic, casein, alginic acid, and salts thereof. Among them, carboxymethylcellulose and polyvinyl alcohol are preferred because they can be easily removed by washing after forming a film using the rubber latex blend. When the rubber latex contains NBR, polyvinyl alcohol is particularly preferred from the viewpoint of film forming processability.
[0049] When polyvinyl alcohol is used as the polymer compound, it may be partially saponified (saponification degree 88 mol % or less), intermediately saponified (saponification degree more than 88 mol % but less than 98 mol %) or completely saponified (saponification degree more than 98 mol %). From the viewpoint of the relationship between the solubility of polyvinyl alcohol and the viscosity of the rubber latex compound, the intermediately saponified polyvinyl alcohol is preferred.
[0050] The lower limit of the mass ratio of the water-soluble polymer to the anionic surfactant is preferably 0.06, more preferably 0.25, and even more preferably 0.5. On the other hand, the upper limit of the mass ratio of the water-soluble polymer is preferably 60, more preferably 15, and even more preferably 10. If the mass ratio of the water-soluble polymer is less than the lower limit, the effect of adding the water-soluble polymer may not be sufficiently obtained. On the other hand, if the mass ratio of the water-soluble polymer is more than the upper limit, the stability of the rubber latex compound may be too high, and the compound may drip during glove molding, resulting in deterioration of moldability.
[0051] The water-soluble polymer prevents the rubber latex compound from being destabilized by the carbon black. In other words, the stability of the carbon black in the rubber latex compound is considered to be determined by the total amount of the nonionic dispersant and the water-soluble polymer. The lower limit of the total mass ratio of the nonionic dispersant and the water-soluble polymer to the anionic surfactant is preferably 0.5, more preferably 2, and even more preferably 4. On the other hand, the upper limit of the total mass ratio is preferably 300, more preferably 120, and even more preferably 50. If the total mass ratio is less than the lower limit, the stability of the carbon black may decrease, resulting in the generation of aggregates and a decrease in electrical conductivity. On the other hand, if the total mass ratio exceeds the upper limit, the stability of the carbon black may become too high, causing the compound to drip during glove molding, and the moldability may deteriorate.
[0052] The lower limit of the amount of the water-soluble polymer to be added relative to 100 parts by mass of the carbon black is 8 parts by mass, more preferably 9 parts by mass. On the other hand, the upper limit of the amount of the water-soluble polymer to be added is 50 parts by mass, more preferably 18 parts by mass. If the amount of the water-soluble polymer to be added is less than the lower limit, aggregation due to the carbon black may easily occur in the rubber latex compound. On the other hand, if the amount of the water-soluble polymer to be added exceeds the upper limit, sagging of the compound may occur during glove molding, resulting in deterioration of moldability.
[0053] The lower limit of the amount of the water-soluble polymer added relative to 100 parts by mass of the solid content of the rubber latex is preferably 0.06 parts by mass, more preferably 0.2 parts by mass, and even more preferably 0.3 parts by mass. On the other hand, the upper limit of the amount of the water-soluble polymer added is preferably 3 parts by mass, more preferably 1.5 parts by mass, and even more preferably 1 part by mass. If the amount of the water-soluble polymer added is less than the lower limit, aggregation due to the carbon black may easily occur in the rubber latex compound. On the other hand, if the amount of the water-soluble polymer added exceeds the upper limit, the stability of the carbon black may become too high, which may cause the compound to drip during glove molding, resulting in poor moldability.
[0054] The lower limit of the total amount of the nonionic dispersant and the water-soluble polymer to be added relative to 100 parts by mass of the carbon black is 38 parts by mass, more preferably 50 parts by mass. On the other hand, the upper limit of the total amount to be added is 200 parts by mass, more preferably 150 parts by mass. If the total amount to be added is less than the lower limit, aggregation due to the carbon black occurs in the rubber latex compound, and the required conductivity may not be obtained. Then, it becomes necessary to secure conductivity by excessive addition, and the glove may become hard. On the other hand, if the total amount to be added exceeds the upper limit, the stability of the rubber latex compound becomes too high, so that the compound may drip during glove molding, which may deteriorate moldability or inhibit the formation of a conductive path of the carbon black.
[0055] The mass ratio of the anionic surfactant, the nonionic dispersant, and the water-soluble polymer in the rubber latex compound is preferably 1:0.2 to 285:0.06 to 60, more preferably 1:1 to 112:0.25 to 15, and even more preferably 1:2.5 to 45:0.5 to 10. The mass ratio of the water-soluble polymer to the nonionic dispersant is preferably 0.1 to 10. By setting the mass ratio of the anionic surfactant, the nonionic dispersant, and the water-soluble polymer within the above ranges, the stability of the carbon black in the rubber latex compound is increased, and a highly conductive glove can be formed without increasing the amount of carbon black added. This makes it possible to provide a soft and highly reactive glove.
[0056] <Other additives> The rubber latex compound may contain additives such as vulcanizing agents, vulcanization accelerators, metal oxides, metal salts, metal oxide salts, pigments, antioxidants, thickeners, alkali stabilizers, heat-sensitive agents, heat-sensitive point depressants, film-forming aids, etc. When the raw materials are foamed with a foaming machine, it is also possible to add known foaming agents and foam stabilizers separately.
[0057] When carboxymethyl cellulose or polyvinyl alcohol is added as the water-soluble polymer, the salt coagulation processability tends to decrease, so it is advisable to add zinc oxide, which is one of the metal oxides. The lower limit of the amount of zinc oxide added relative to 100 parts by mass of the solid content of the rubber latex is preferably 1.0 part by mass, and more preferably 1.5 parts by mass. Meanwhile, the upper limit of the amount of zinc oxide added is preferably 5 parts by mass, and more preferably 3.5 parts by mass. By adding zinc oxide in an amount within the above range, it is possible to prevent a decrease in coagulation processability. It is also preferable to use a heat-sensitive agent in combination to create a compounding system in which the viscosity increases due to heat.
[0058] In order to improve the mechanical stability of the latex compound, an alkali stabilizer may be added to adjust the pH to 9.0 or more and 11.2 or less. Examples of the alkali stabilizer include potassium hydroxide and ammonia.
[0059] <Method for producing rubber latex compound> The rubber latex compound can be produced by a production method including a step of adding the carbon black, the anionic surfactant, the nonionic dispersant, and the water-soluble polymer to the rubber latex.
[0060] The rubber latex is preferably adjusted to a low viscosity in advance by dilution, which makes it easier to disperse the carbon black.
[0061] The upper limit of the viscosity of the rubber latex after the above adjustment before adding the carbon black, the anionic surfactant, and the nonionic dispersant is preferably 1000 mPa·s, more preferably 500 mPa·s, as measured using a B-type viscometer. On the other hand, depending on the amount of dilution, the proportion of solids decreases, and the thickness of the coating during molding becomes thin, but there is no particular limitation as long as there is no effect on processability. The lower limit of the viscosity of the rubber latex after the above adjustment can be, for example, 10 mPa·s.
[0062] As described above, the carbon black is preferably prepared as an aqueous dispersion dispersed with the nonionic dispersant. The addition to the rubber latex is preferably performed in the order of the water-soluble polymer, the carbon black, and the aqueous dispersion containing the nonionic dispersant. The order of addition of the anionic surfactant is not particularly limited, but is preferably before the addition of the water-soluble polymer.
[0063] When other additives are added, they are preferably added after the addition of the anionic surfactant. The order of addition of the water-soluble polymer and other additives does not matter.
[0064] <Advantages> The rubber latex compound contains carbon black having a DBP oil absorption of 250 ml / 100 g or more and 600 ml / 100 g or less and a volatile content of 0.3 mass % or more and less than 1.0 mass %, so that it is easy to improve compounding stability and ensure the conductivity of the formed coating. The rubber latex compound also contains a nonionic dispersant and a water-soluble polymer, the amount of which is 8 parts by mass or more and 50 parts by mass or less per 100 parts by mass of the carbon black, and the total amount of the nonionic dispersant and the water-soluble polymer is 38 parts by mass or more and 200 parts by mass or less per 100 parts by mass of the carbon black, and further contains an anionic surfactant. This compounding can improve the compounding stability of the carbon black in the rubber latex compound. Therefore, in the coating formed using the rubber latex compound, it is easy to ensure conductive paths in which the carbon blacks are connected to each other and extend, and high conductivity is shown with a small amount added. Therefore, by using the rubber latex compound, it is possible to produce gloves having excellent touch panel responsiveness and high flexibility.
[0065] [Glove manufacturing method] A method for manufacturing a glove according to another embodiment of the present invention includes a first dipping step S1 of dipping a hand mold into a coagulant solution, a second dipping step S2 of dipping the hand mold after the first dipping step S1 into a rubber latex compound, and a drying step S3 of drying the hand mold after the second dipping step S2, as shown in Fig. 1. In the method for manufacturing a glove, the rubber latex compound is the rubber latex compound of the present invention.
[0066] [First embodiment] By using this glove manufacturing method, it is possible to manufacture a glove 1, which is itself an embodiment of the present invention, as shown in Figures 2 and 3.
[0067] <Gloves> The glove 1 includes a conductive portion 1a exposed at least on the outer surface of the palm side of the second finger region A. Specifically, the glove 1 includes a fiber knitted glove body 10 and a coating layer 20 that constitutes the conductive portion 1a.
[0068] (Knitted glove body) The knitted glove body 10 has a main body portion 10a formed in a bag shape to cover the palm and back of the hand of a wearer, bottomed, tubular first to fifth finger portions 10b extended from the main body portion 10a to cover the wearer's first to fifth fingers, respectively, and a tubular hem portion 10c extended in the opposite direction from the first to fifth finger portions 10b.
[0069] Examples of the yarn constituting the knitted glove body 10 include cotton yarn, polyester yarn, nylon yarn, polyethylene yarn, polypropylene yarn, acrylic yarn, para-aramid yarn, meta-aramid yarn, polyparaphenylenebenzoxazole (PBO) yarn, ultra-high molecular weight polyethylene yarn, stretched polyethylene yarn, glass fiber yarn, metal fiber yarn, composite yarn thereof, etc. In addition, elastic yarn made of natural rubber, polyurethane, etc. can also be used in order to impart stretchability.
[0070] The yarn constituting the knitted glove body 10 may be a single yarn or a double-ply yarn such as a spun yarn, a filament yarn, or a composite yarn. When a spun yarn is used as the yarn, a yarn having a thickness equivalent to a cotton count of 3.3 or more and 100 or less when the single yarn, the double-ply yarn, etc. are combined may be used. When a filament yarn is used as the yarn, a yarn having a thickness equivalent to a cotton count of 50 dtex or more and 1500 dtex or less when the single yarn, the double-ply yarn, etc. are combined may be used. When both a spun yarn and a filament yarn, or a composite yarn of these, a thickness equivalent to a cotton count of 50 dtex or more and 1500 dtex or less when all the yarns are combined may be used.
[0071] It is preferable that the knitted glove body 10 contains conductive fibers. By combining the knitted glove body 10 containing conductive fibers with the conductive part 1a, static electricity discharge is suppressed, and therefore explosion-proof properties that prevent fires and explosions caused by flammable gases, steam, dust, etc. can be improved.
[0072] Examples of the conductive fibers include carbon composite organic fibers, metal oxide composite organic fibers, metal compound composite organic fibers, and metal-plated organic fibers. For example, Kuracarbo (registered trademark) manufactured by Kuraray Co., Ltd., Vectron (registered trademark) manufactured by Seiren Co., Ltd., Thunderon (registered trademark) manufactured by Nippon Sanmo Dyeing Co., Ltd., and AGposs (registered trademark) manufactured by Mitsufuji Co., Ltd. can be used.
[0073] (Coating layer) The coating layer 20, i.e., the conductive portion 1a, is laminated on the outer surface side of the knitted glove body 10. In the glove 1 shown in Figures 2 and 3, the conductive portion 1a is formed on the entire surface of the knitted glove body 10 except for a part of the hem portion 10c on the palm side, but it is sufficient that the conductive portion 1a is formed on at least the outer surface on the palm side of the second finger region A.
[0074] The coating layer 20 is preferably a foamed structure, which is formed by using the rubber latex compound of the present invention and forming and solidifying it on the surface of the knitted glove body 10. By making it into such a foamed structure, the flexibility of the coating layer 20 is improved, which makes it easier to conform to the touch panel, thereby improving the responsiveness of the touch panel.
[0075] When the coating layer 20 has a foamed structure, the air content in the coating layer 20 is preferably 10% or more and 60% or less. By setting the air content to be equal to or more than the lower limit, flexibility can be increased. On the other hand, by setting the air content to be equal to or less than the upper limit, the strength of the coating layer 20 can be maintained. The "air content" is determined by observing the cross section of a test piece cut from the center of the palm under a microscope at 100x to 200x magnification, and judging the proportion of voids in the coating portion.
[0076] The conductive portion 1a is mainly composed of rubber and also contains carbon black.
[0077] The main rubber component may be the same as the rubber component of the rubber latex contained in the rubber latex compound of the present invention.
[0078] The carbon black may be the same as the carbon black contained in the rubber latex compound of the present invention.
[0079] The lower limit of the amount of carbon black added to 100 parts by mass of the rubber in the conductive part 1a is 0.6 parts by mass, more preferably 2 parts by mass, and even more preferably 3 parts by mass. On the other hand, the upper limit of the amount of carbon black added is 9.5 parts by mass, more preferably 8 parts by mass, and even more preferably 7 parts by mass. If the amount of carbon black added is less than the lower limit, the conductivity may be insufficient. On the other hand, if the amount of carbon black added is more than the upper limit, the flexibility may be insufficient, and for example, the operability of a touch panel may be deteriorated.
[0080] The lower limit of the surface resistance of the conductive portion 1a is 10 3 Ω and 10 4 On the other hand, the upper limit of the surface resistance of the conductive portion 1a is 10 8 Ω. In order to make the surface resistance value of the conductive part 1a less than the lower limit, it is necessary to increase the amount of the carbon black added, which may result in insufficient flexibility and, for example, a poor operability of the touch panel. Conversely, if the surface resistance value of the conductive part 1a exceeds the upper limit, the responsiveness of the touch panel may deteriorate.
[0081] The lower limit of the volume resistance of the conductive portion 1a is 10 3 Ω is preferred, 10 4 On the other hand, the upper limit of the volume resistance of the conductive portion 1a is 10 8 Ω is preferable. In order to make the volume resistance value of the conductive part 1a less than the lower limit, it is necessary to increase the amount of the carbon black added, which may result in insufficient flexibility and, for example, a poor operability of a touch panel. On the other hand, if the volume resistance value of the conductive part 1a exceeds the upper limit, it may be difficult to impart high explosion-proof properties.
[0082] The upper limit of the modulus of the conductive part 1a at 30% elongation is preferably 25 N / cm, more preferably 18 N / cm, and even more preferably 13 N / cm. If the modulus exceeds the upper limit, the flexibility is insufficient, and for example, the operability of a touch panel may deteriorate. On the other hand, the lower limit of the modulus is not particularly limited, but is preferably 1 N / cm, more preferably 2 N / cm, from the viewpoint of maintaining the strength of the glove. The "modulus at 30% elongation" can be measured by the following method. A test piece of 1 cm x 6 cm is cut out from the finger part of the glove, set on a chuck spaced 40 mm apart, and pulled at a tensile speed of 500 mm / min. The modulus value at 30% elongation is the modulus value at 30% elongation for this test piece. This is performed for four test pieces, and the arithmetic average is taken as the modulus at 30% elongation.
[0083] The lower limit of the average thickness of the conductive part 1a is preferably 0.1 mm, more preferably 0.15 mm. On the other hand, the upper limit of the average thickness of the conductive part 1a is preferably 1.0 mm, more preferably 0.8 mm, and even more preferably 0.6 mm. If the average thickness of the conductive part 1a is less than the lower limit, the wear resistance of the conductive part 1a may decrease, and it may be difficult to ensure conductivity. On the other hand, if the average thickness of the conductive part 1a exceeds the upper limit, the flexibility may be insufficient, and for example, the operability of a touch panel may be deteriorated. The "average thickness" is the arithmetic average of the thicknesses of 20 points measured at intervals of 200 μm over a width of 4 mm by observing the cross section of a test piece cut from the center of the palm in the longitudinal direction of the finger at a magnification of 50 times.
[0084] <Manufacturing method of the glove> Each step of the manufacturing method of the glove 1 will be described below.
[0085] (1st dipping step) In the first dipping step S1, the prepared knitted glove body 10 is placed over a hand mold, the hand mold is dipped in the coagulant solution, and then pulled out, and the solvent of the coagulant solution is evaporated. The prepared knitted glove 10 can be made by knitting the above-mentioned yarn on a glove knitting machine with a gauge of 13 or more and 26 or less.
[0086] The coagulant solution may be a known one, such as a methanol solution or an aqueous solution containing a polyvalent metal salt or an organic acid. Among them, it is preferable to contain a polyvalent metal salt. By including a polyvalent metal salt in the coagulant solution, it is easy to prevent excessive penetration of the rubber latex for forming the coating layer 20 into the knitted glove body 10.
[0087] Examples of the polyvalent metal salt include barium chloride, calcium chloride, magnesium chloride, zinc chloride, aluminum chloride, barium nitrate, calcium nitrate, zinc nitrate, barium acetate, calcium acetate, zinc acetate, calcium sulfate, magnesium sulfate, aluminum sulfate, etc. These may be used alone or in combination of two or more.
[0088] The lower limit of the content of the polyvalent metal salt in the coagulant solution is preferably 0.1 parts by mass, more preferably 0.3 parts by mass, and even more preferably 0.5 parts by mass, relative to 100 parts by mass of the solvent. On the other hand, the upper limit of the content of the polyvalent metal salt is not particularly limited as long as it can prevent the coating layer 20 from peeling off from the knitted glove body 10, but is preferably 5 parts by mass, and more preferably 4 parts by mass, relative to 100 parts by mass of the solvent.
[0089] Examples of the organic acid include acetic acid and citric acid. The content of the organic acid in the coagulant solution is preferably 5 parts by mass or more and 50 parts by mass or less per 100 parts by mass of the solvent. The organic acid can be used alone, but is preferably used in combination with a polyvalent metal salt. By using the organic acid in combination with a polyvalent metal salt, it is possible to prevent the thickness of the coating layer 20 from becoming thin. In addition, it is easier to control the film forming ability of the coagulant solution than when each is used alone.
[0090] The temperature of the hand mold when it is immersed in the coagulant solution is preferably 40° C. or higher and 70° C. or lower, from the viewpoint of the penetration of the coagulant into the knitted glove body 10.
[0091] The temperature at which the solvent is evaporated after immersion in the coagulant solution and removal is preferably 25°C or more and 70°C or less, and the lower limit of the time for evaporating the solvent (volatilization time) is preferably 10 seconds. On the other hand, the upper limit of the volatilization time is not particularly limited, but is preferably 600 seconds from the viewpoint of productivity. This volatilization of the solvent can control the penetration of the rubber latex in the next process, so that the coating layer 20 can be prevented from penetrating into the knitted glove body 10 and deteriorating the feel of the inner surface of the glove, while preventing the formed coating layer 20 from peeling off. From the viewpoint of controlling the penetration of the rubber latex, when the solvent is methanol, the volatilization time is more preferably 10 seconds or more and 180 seconds or less, and when the solvent is water, it is more preferably 30 seconds or more and 600 seconds or less.
[0092] (Second dipping step) In the second dipping step S2, the hand mold covered with the knitted glove body 10 after the first dipping step S1 is dipped into the rubber latex compound and then pulled out.
[0093] When the covering layer 20 has a foamed structure, it is preferable to use the rubber latex compound foamed by a foaming machine.
[0094] (drying process) In the drying step S3, the moisture in the latex coating formed by immersion in the rubber latex compound is evaporated. This drying step S3 can be performed using, for example, a known oven.
[0095] The temperature at which the moisture is evaporated is preferably 50° C. or higher and 100° C. or lower. If the temperature is below the lower limit, the wet latex coating may sag, resulting in a non-uniform coating layer 20. Conversely, if the temperature exceeds the upper limit, drying may be uneven due to rapid drying, resulting in a non-uniform coating layer 20.
[0096] It is preferable to include a solidification step in which the coating layer 20 is solidified at a temperature of 100° C. to 140° C. when the moisture content in the coating layer 20 is reduced. In addition, an additive removal step in which additives that have bled or bloomed from the coating layer 20 are removed by washing with water before the solidification step may be incorporated into the drying process. In the additive removal step, washing with water before the solidification step is preferable in that discoloration of the knitted glove body 10 and the coating layer 20 is prevented.
[0097] From the viewpoint of manufacturing efficiency, the time for evaporating water in the drying step S3 is preferably 10 minutes or more and 80 minutes or less, and the time for solidification in the solidification step is preferably 10 minutes or more and 80 minutes or less.
[0098] The second immersion step S2 and the drying step S3 may be repeated multiple times. By performing these steps multiple times, the uniformity of the formed coating layer 20 is improved. From the viewpoint of manufacturing efficiency, the number of repetitions is preferably three or less.
[0099] <Advantages> In the manufacturing method of the gloves, the rubber latex compound of the present invention is used as the rubber latex compound, so that it is easy to secure conductive paths in which carbon black particles are connected to each other, and it is possible to manufacture gloves having excellent touch panel responsiveness and high flexibility.
[0100] In addition, the glove 1 obtained by the manufacturing method of the glove has a surface resistance of 10 3 Ω or more 10 8 It has high conductivity of Ω or less. In other words, it is considered that a large number of conductive paths in which carbon black particles are connected to each other are secured in the glove 1. Therefore, the glove 1 has excellent touch panel responsiveness and high flexibility.
[0101] [Second embodiment] By using the glove manufacturing method shown in FIG. 1, a glove 2 shown in FIG. 4 can also be manufactured.
[0102] <Gloves> The glove 2 includes a conductive portion 2a exposed at least on the outer surface of the palm side of the second finger region A. Specifically, the glove 2 includes a coating 30 that constitutes the conductive portion 2a.
[0103] The covering 30 has a main body portion 30a formed in a bag shape to cover the wearer's hand, five finger portions 30b extending from the main body portion 30a to cover the wearer's first to fifth fingers, and a tubular hem portion 30c extending from the main body portion 30a in the opposite direction to the finger portions 30b to cover the wearer's wrist.
[0104] The coating 30, ie, the conductive portion 2a, is mainly composed of rubber and also contains carbon black.
[0105] The main rubber component may be the same as the rubber component of the rubber latex contained in the rubber latex compound of the present invention.
[0106] The carbon black may be the same as the carbon black contained in the rubber latex compound of the present invention.
[0107] The lower limit of the amount of carbon black added to 100 parts by mass of the rubber in the conductive part 2a is 0.6 parts by mass, more preferably 2 parts by mass, and even more preferably 3 parts by mass. On the other hand, the upper limit of the amount of carbon black added is 9.5 parts by mass, more preferably 8 parts by mass, and even more preferably 7 parts by mass. If the amount of carbon black added is less than the lower limit, the conductivity may be insufficient. On the other hand, if the amount of carbon black added exceeds the upper limit, the flexibility may be insufficient, and for example, the operability of a touch panel may be deteriorated.
[0108] The lower limit of the surface resistance of the conductive portion 2a is 10 3 Ω and 10 4 On the other hand, the upper limit of the surface resistance of the conductive portion 2a is 10 8Ω. In order to make the surface resistance value of the conductive part 2a less than the lower limit, it is necessary to increase the amount of the carbon black added, which may result in insufficient flexibility and, for example, a deterioration in the operability of the touch panel. Conversely, if the surface resistance value of the conductive part 2a exceeds the upper limit, for example, the responsiveness of the touch panel may deteriorate.
[0109] The lower limit of the volume resistance of the conductive portion 2a is 10 3 Ω is preferred, 10 4 On the other hand, the upper limit of the volume resistance of the conductive portion 2a is 10 8 Ω is preferable. In order to make the volume resistance value of the conductive part 2a less than the lower limit, it is necessary to increase the amount of the carbon black added, which may result in insufficient flexibility and, for example, a poor operability of a touch panel. On the other hand, if the volume resistance value of the conductive part 2a exceeds the upper limit, it may be difficult to impart high explosion resistance.
[0110] The upper limit of the modulus of the conductive part 2a at 30% elongation is preferably 12 N / cm, more preferably 10 N / cm, and even more preferably 8 N / cm. If the modulus exceeds the upper limit, the flexibility is insufficient, and for example, the operability of a touch panel may be deteriorated. On the other hand, the lower limit of the modulus is not particularly limited, but is preferably 0.3 N / cm, and more preferably 0.5 N / cm, from the viewpoint of maintaining the strength of the glove.
[0111] The lower limit of the average thickness of the conductive part 2a is preferably 0.06 mm, more preferably 0.08 mm. On the other hand, the upper limit of the average thickness of the conductive part 1a is preferably 0.4 mm, more preferably 0.3 mm. If the average thickness of the conductive part 1a is less than the lower limit, the strength of the conductive part 2a may be insufficient, and it may be difficult to ensure conductivity. On the other hand, if the average thickness of the conductive part 1a exceeds the upper limit, the flexibility may be insufficient, and for example, the operability of the touch panel may be deteriorated.
[0112] <Manufacturing method of the glove> Each step of the manufacturing method of the glove 2 will be described below.
[0113] (1st dipping step) In the first dipping step S1, the hand mold is directly dipped into the coagulant solution, and after being pulled out, the solvent of the coagulant solution is evaporated.
[0114] The coagulant solution may be the same as that used in the first immersion step S1 described in the first embodiment, except that the content of the polyvalent metal salt used is 5 parts by mass or more and 100 parts by mass or less per 100 parts by mass of the solvent. In addition, the temperature of the hand mold when immersing the hand mold in the coagulant solution, the temperature at which the solvent is evaporated, and the time at which the solvent is evaporated may also be the same as those in the first immersion step S1 described in the first embodiment, and therefore detailed explanations will be omitted.
[0115] (Second dipping step) In the second dipping step S2, the hand mold after the first dipping step S1 is dipped into the rubber latex compound and then pulled out.
[0116] From the viewpoint of moldability, the average thickness of the latex coating formed by one immersion is preferably 0.05 mm to 0.6 mm. In other words, when forming a thick coating 30, it is preferable to form the coating 30 by immersing the rubber latex compound multiple times. When the above immersion is performed multiple times, the second immersion step S2 and the drying step S3 described below may be repeated multiple times to evaporate the water in the latex coating between immersions.
[0117] (drying process) In the drying step S3, the moisture in the latex coating formed by immersion in the rubber latex compound is evaporated. The drying step S3 can be performed in the same manner as the drying step S3 described in the first embodiment.
[0118] <Advantages> By using this glove manufacturing method, even a glove 2 consisting of only the coating film 30 can be made to have excellent touch panel responsiveness and high flexibility.
[0119] [Other embodiments] The present invention is not limited to the above-described embodiment, and can be embodied in various other forms in addition to the above-described forms with various modifications and improvements.
[0120] The coating layer of the glove of the first embodiment or the coating of the glove of the second embodiment may be provided with irregularities to impart anti-slip effect or visual effect to the glove. As a method for providing irregularities to the coating layer or the coating, for example, a method of forming desired irregularities on a hand mold in advance and transferring the shape of the irregularities can be mentioned. EXAMPLES
[0121] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0122] [Rubber latex compound] <No.1> As the rubber latex, "Lx550" manufactured by Zeon Corporation, which is an NBR latex, was prepared.
[0123] The carbon black used was "W311N" manufactured by Lion Specialty Chemicals, a water dispersion containing conductive carbon (the specific surface area of the conductive carbon is 800 m 2 The carbon black aqueous dispersion was prepared using a non-ionic dispersant. The amount of the non-ionic dispersant added per 100 parts by mass of the carbon black was 102 parts by mass.
[0124] As an anionic surfactant, Kao Corporation's "Neopelex G-15" (sodium dodecylbenzenesulfonate (soft type)) was prepared. In addition, Kuraray Co., Ltd.'s polyvinyl alcohol "Poval PVA217" (saponification degree 88 mol%, partial to intermediate saponification) was prepared as a water-soluble polymer.
[0125] 0.2 parts by mass of the anionic surfactant was added to the NBR latex as a 16% by mass aqueous solution relative to 100 parts by mass of the solid content of the NBR latex, and then 0.3 parts by mass of the water-soluble polymer was added as a 10% by mass aqueous solution and stirred for 10 minutes. Next, the carbon black aqueous dispersion was added so that the carbon black solid content was 2.5 parts by mass (nonionic dispersant was 2.6 parts by mass) relative to 100 parts by mass of the solid content of the NBR latex, and after stirring for 30 minutes, the additives shown in Table 1 were added in the amounts (solid content) shown in Table 1 as other additives to obtain No. 1 rubber latex compound. The solid content of the rubber latex compound was 43% by mass, and the remainder was water.
[0126] [Table 1]
[0127] <No.2~No.24> Rubber latex compounds No. 2 to No. 24 were obtained in the same manner as No. 1, except that the type of rubber latex, the amount of carbon black added, and the type and amount of water-soluble polymer added were as shown in Table 3.
[0128] In Table 3, "LATZ" manufactured by SUNWISE was used as the NR rubber latex. When the NR rubber latex was used, the types and amounts (solid content) of other additives were as shown in Table 2, the solid content of the rubber latex compound was 54 mass%, and the remainder was water.
[0129] [Table 2]
[0130] As for the type of water-soluble polymer, PVA217 indicates the "Poval PVA217" used in No. 1. PVA117 and PVA424H are polyvinyl alcohols manufactured by Kuraray Co., Ltd., "Poval PVA117" (saponification degree 98 mol%, fully saponified) and "Poval PVA424H" (saponification degree 80 mol%, partially saponified), respectively. 65SH50 and SM400 are methylcelluloses manufactured by Shin-Etsu Chemical Co., Ltd., "Metolose 65SH50" (hydroxypropyl methylcellulose) and "Metolose SM400" (methylcellulose), respectively. "-" indicates that no water-soluble polymer was added.
[0131] [evaluation] The mechanical stability and film-forming properties of rubber latex compounds No. 1 to No. 24 were examined.
[0132] <Mechanical stability> Using a turbine-type impeller in a BL600 mixer manufactured by HEIDON, 500 g of the rubber latex compound was stirred at 200 rpm under a constant jacket temperature of 23°C. The time until the rubber latex compound gelled was then visually observed and evaluated according to the following criteria. The results are shown in Table 3. (Evaluation Criteria) A: It was stable for more than 7 days. B: Aggregated on the fourth day C: Aggregated in 18 hours D: Aggregated in 2 hours
[0133] <Film forming properties> Film gloves were prepared and the film-forming properties of the coating were evaluated according to the following criteria. The results are shown in Table 3. (Evaluation Criteria) A: No cracks observed, good condition B: The cracks are minute and do not pose any problems in use. C: Cracks occurred
[0134] The gloves were prepared according to the following procedure, which differed between the NBR rubber latex compound and the NR rubber latex compound.
[0135] (Preparation of gloves using NBR rubber latex compound) A ceramic hand mold without a surface coating, which had been heated in a 70°C oven, was immersed in a coagulant (a methanol solution of 29% by mass calcium nitrate) and dried in an oven at 70°C for 1 minute. The hand mold was then immersed in an NBR rubber latex compound, and then dried and vulcanized in an oven at 60°C for 1 hour and at 130°C for 35 minutes. The film was removed from the hand mold while being inverted, leached in 30°C water for 45 minutes, and then dried in an oven at 70°C for 60 minutes to obtain the desired film-like glove.
[0136] (Glove preparation when using NR rubber latex compound) A ceramic hand mold without a surface coating, which had been heated in an oven at 70°C, was immersed in a coagulant (a methanol solution of 29% by mass calcium nitrate) and dried in an oven at 70°C for 1 minute. The hand mold was then immersed in an NR rubber latex compound, and then dried and vulcanized in an oven at 60°C for 1 hour and at 115°C for 35 minutes. The film was removed from the hand mold, leached in water at 30°C for 45 minutes, and then dried in an oven at 70°C for 60 minutes to obtain the desired film-like glove.
[0137] [Table 3]
[0138] From the results in Table 3, it can be seen that the rubber latex blends No. 1 to No. 17 in which the amount of water soluble polymer added to 100 parts by mass of carbon black is 8 parts by mass or more and 50 parts by mass or less, and the total amount of nonionic dispersant and water soluble polymer added to 100 parts by mass of carbon black is 38 parts by mass or more and 200 parts by mass or less, are excellent in mechanical stability and film forming property of gloves.
[0139] On the other hand, the rubber latex compounds No. 18 to No. 20 and No. 22 to No. 24, in which the amount of the water-soluble polymer added is less than 8 parts by mass, are inferior in mechanical stability, and No. 21, in which the total amount of the nonionic dispersant and the water-soluble polymer added exceeds 200 parts by mass, is inferior in film-forming property.
[0140] From the above, it can be said that by setting the amount of water soluble polymer to be added to 8 parts by mass or more and 50 parts by mass or less, and by setting the total amount of nonionic dispersant and water soluble polymer to be added to 100 parts by mass of carbon black to 38 parts by mass or more and 200 parts by mass or less, a rubber latex compound excellent in mechanical stability and film forming property of a glove can be obtained.
[0141] [gloves] Using the rubber latex compound shown in Table 4 (rubber latex compound No. 2 in Table 3), glove No. 25 was produced, which had a fiber knitted glove body and a coating layer constituting a conductive part. The glove production procedure is as follows.
[0142] (Making gloves No. 25) The glove body was knitted using a composite yarn made of woolly nylon 312dtex (two double-ply yarns of 78dtex-24f) as the core yarn and carbon composite organic fiber 22dtex-3f (KB Seiren's "9R1") wrapped around it at 300T / M using Shima Seiki's "N-SFG 13G". The average thickness was 0.80mm.
[0143] The viscosity of the NBR rubber latex compound shown in Table 4 was adjusted to 1500 mPa·s (B-type viscometer) using a thickener (Toa Gosei Co., Ltd. "A-7075"). Next, the knitted glove body was placed on a metal hand mold, and the hand mold, which had been heated in an oven at 70°C, was immersed in a coagulant (1.0 mass% calcium nitrate methanol solution) and then dried at room temperature for 30 seconds. The hand mold was then immersed in the NBR rubber latex compound, dried at 85°C for 20 minutes, released, leached in water at 30°C for 45 minutes, vulcanized at 130°C for 35 minutes, and removed from the hand mold to obtain the desired glove. The average thickness of the coating layer was 0.35 mm.
[0144] [evaluation] The gloves No. 25 and No. 2 were evaluated for surface resistance, volume resistance, touch panel operability and modulus at 30% elongation.
[0145] (Surface resistance and volume resistance) The surface resistance and volume resistance were measured according to the EN standards EN16350 and EN61340-2-3:2016 8, respectively. Specifically, a test piece was cut from the palm of the prepared glove, and a concentric ring electrode was used to connect the resistance meter "PRS-812" manufactured by PROSTAT according to the measurement procedure for surface resistance and volume resistance of the above standard, and the displayed resistance value (Ω) was read. The results are shown in Table 4.
[0146] (Touch panel operability) Nylon cylindrical rod (cross-sectional area 16.3 mm 2 The results are shown in Table 4. (Evaluation Criteria) A: Move without stress B: I feel a little stressed C: No movement at all, or difficulty in touching the desired spot
[0147] (Modulus at 30% elongation) Four test pieces measuring 1 cm x 6 cm were cut from the finger of the glove, set in chucks spaced 40 mm apart, and pulled at a tensile speed of 500 mm / min to measure the modulus at 30% elongation, and the average value was taken as the modulus at 30% elongation. The results are shown in Table 4.
[0148] [Table 4]
[0149] From the results in Table 4, all the gloves have excellent touch panel operation. In addition, the modulus at 30% elongation is 8N / cm or less, indicating high flexibility. From the above, it can be seen that by using the rubber latex compound of the present invention, gloves having excellent touch panel responsiveness and high flexibility can be obtained regardless of the glove shape. [Industrial Applicability]
[0150] As described above, the rubber latex compound of the present invention can be used to produce gloves having excellent touch panel responsiveness and high flexibility. Also, possible rubber latex compounds, gloves produced using the rubber latex compounds, and the gloves of the present invention have excellent touch panel responsiveness and high flexibility. [Explanation of symbols]
[0151] 1, 2 Gloves 1a, 2a Conductive part 10 Knitted glove body 10a Main body 10b Finger part 10c hem 20 Coating layer 30 Coating 30a Main body 30b Finger part 30c hem A 2nd finger area
Claims
1. A rubber latex compound for gloves containing rubber latex as a main component, Carbon black, an anionic surfactant, a nonionic dispersant, and a water-soluble polymer are added, the carbon black has a DBP oil absorption of 250 ml / 100 g or more and 600 ml / 100 g or less and a volatile content of 0.3 mass % or more and less than 1.0 mass %, the amount of the water-soluble polymer added per 100 parts by mass of the carbon black is 8 parts by mass or more and 50 parts by mass or less; A rubber latex compound, wherein the total amount of the nonionic dispersant and the water-soluble polymer added per 100 parts by mass of the carbon black is 38 parts by mass or more and 200 parts by mass or less.
2. 2. The rubber latex compound according to claim 1, wherein the amount of the carbon black added is 0.6 parts by mass or more and 9.5 parts by mass or less based on 100 parts by mass of the solid content of the rubber latex.
3. 3. The rubber latex compound according to claim 1, wherein the amount of the anionic surfactant added is 0.05 part by mass or more and 1.0 part by mass or less based on 100 parts by mass of the solid content of the rubber latex.
4. 4. The rubber latex compound according to claim 1, wherein a mass ratio of the nonionic dispersant to the anionic surfactant is 0.2 or more and 285 or less.
5. 5. The rubber latex compound according to claim 1, wherein a total mass ratio of the nonionic dispersant and the water-soluble polymer to the anionic surfactant is 0.5 or more and 300 or less.
6. A first dipping step of dipping the hand mold into a coagulant solution; a second dipping step of dipping the hand mold after the first dipping step into a rubber latex compound; a drying step for drying the hand mold after the second dipping step; Equipped with A method for producing a glove, wherein the rubber latex compound is the rubber latex compound according to any one of claims 1 to 5.
7. A knitted glove body made of fiber; A conductive portion exposed on at least the outer surface of the palm side of the second finger region; Equipped with The conductive portion is mainly composed of rubber and contains carbon black, The amount of carbon black added per 100 parts by mass of the rubber is 0.6 parts by mass or more and 9.5 parts by mass or less, the conductive portion has a surface resistance value of 10 3 Ω or more and 10 8 Ω or less; The knitted glove body includes conductive fibers, The conductive portion is laminated on the outer surface side of the knitted glove body. 【Request 8】 The volume resistance of the conductive portion is 10 3 Ω or more 10 8 The glove according to claim 7, having a hardness of Ω or less.
Citation Information
Patent Citations
Butyronitrile latex-based slurry for multifunctional labor protection gloves and preparation method thereof
CN111253640A
Anti-static latex material, latex gloves and preparation method
CN112538195A
Production of antistatic glove
JP1988075179A
Electrically conductive aqueous emulsion
JP1989045469A
Antistatic rubber latex composition and antistatic rubber glove
JP2003321581A